SWOT dan Critical Success Factor dalam Perencanaan Strategi Sistem Informasi - Dodemand, Flo (E-Jurnal Universitas Samudra, 2024)
There's a logical reason why strategic information system planning should be done. The research was conducted at the IFTK in Ledalero, Flores. This research is based on the current critical conditions of concern, namely how institutions determine business needs and choose SI applications that respond to organizational needs and support decision-making. With the change of shape from a college to an institute, the business needs of the organization are increasing, so the in-depth analysis of the needs of IS is important because it mainly supports decision-making. The findings of this research are the existing IS, some of which are in the operational key quadrant and most of them in the support quadrant. This research is quantitative. Information was obtained through questionnaires and interviews during observations. Data analysis using SWOT and CSF. SWOT provides a strategic overview of organization needs based on analysis of internal and external aspects, while the CSF scheme matrix determines the organization's business needs, the key to success in achieving organizational business requirements, IS needs and solutions offered. The results of this research are an overview of current and future business needs and recommendations for future application portfolios that respond to the business needs of the organization